Modified version of the theory of planned behaviour to study the purchase intention towards Gold Dinar - Peredaryenko, Margarita Sergeevna (2019)
This study explores the literature concerning the purchase intention of gold dinar in Malaysia. Although some research has been done on gold dinar acceptance in the past, a thorough marketing research perspective has been missing in this niche. Yet the gold dinar market is quite dynamic with many public and private initiatives yielding mixed responses from the public. The literature suggests that the theory of planned behaviour is a good analytical approach to understand the purchase intention of Malaysian customers. However, the author of this theory, Ajzen, has discarded the construct of knowledge as irrelevant to the process of formation of behavioural intention. On the other hand, the competing cognitive behavioural theories postulate knowledge as an important variable, at least in the context of consumer behaviour. Thus, this study proposes a modified version of the theory of planned behaviour that includes objective product knowledge and subjective productive knowledge as exogenous variables. A conceptual framework is presented with attitude and behavioural control as mediators. A total of 16 hypotheses were generated.